(untitled) (El-Wahat Journal for Research and Studies, 2017)
This Study Seeks To Uncover The Relationship Between Writing In The Technical Experience And Its Counterpart Mysticism Through The Vision Of The Term, Which Has Become A Link Point Between The Two Experiments In Contemporary Literature, The Purpose For That Was The Experience For A Cluster Of Poets Of Poem Movement Which Is Working Hard To Set The Spiritual Nature Of Creativity, And Restore The Relationship Between The L Poet Individuality And His The Work, In Which He Recalls The Deep Self Experiences And Through Which He Brings Back Via The Language Synonym Of The Expression And Expressed That From The Self Point Of View Emerges The Expressive Language And From That Vision, The Poet Becomes The Conscience Of The Expressed. Keywords - The Vision ,Escetic, Poem Movement , Poetic Writing